Probabilidade geométrica no Ensino Médio: Uma experiência usando o Geogebra - Araújo, Erisvandro Américo de (2017)
The objective of this work was to introduce basic concepts of Geometric Probability, aiming mainly to address treatable problems in High School with the use of GeoGebra software and was developed in classes of 2nd Year of High School of the Padre João Bosco State School of Lima, in the city of Mauriti, Ceará. The idea is to attract the interest of the student to a subject of relative importance in Mathematics that is little approached in High School and to promote the investigation and experimentation of this theme. This was done by approaching problems that are almost always unknown by many high school teachers and also by the absolute majority of students who are at this level of schooling. This work has brought to me new perspectives in the teaching of Geometric Probability and to my students a knowledge that will be of great relevance in their academic lives. Finally, through this work it was possible to conﬁrm that the use of the software can help and foster the teaching process to obtain a more constructive and pleasant learning to the teacher and students.